PEMANFAATAN LIMBAH CAIR TAHU UNTUK PERTUMBUHAN DAN PRODUKSI TANAMAN PAKCOY ( Brassica rapa L.) - Ahmad Al Amin; Arnis En Yulia; Nurbaiti Nurbaiti (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The research was aimed to determine the use of tofu liquid waste to growth and production of pakcoy (Brassica rapa L.) This research has been conducted in the experimental garden of Faculty of Agriculture, University of Riau, Jalan Bina Widya, Baru Simpang Village, District Tampan, Pekanbaru. This research was carried out for 2 months from the month of April - Mei 2017. The study was conducted experimentally using a completely randomized design (CRD) consisting of one Factor that concentration of tofu liquid waste with 5 treatments and 4 replications. The treatments used are as follows: 0%, 12,5%, 25%, 37,5% and 50%. The parameters observed, plant height, leaf number, leaf area, plant fresh weight and fresh weight of plants suitable for consumption. The results showed that given of some tofu liquid waste influencing pakcoy on all parameters, and given of 25% is the most effective concentrations for the growth and production of pakcoy. Keywords: pakcoy, growth and production, tofu liquid waste